“We Might Give People a Sense of the Magnitude of the Problem”: On the Truth Discourse about Violence against Women in the First Phase of Polish #MeToo (#JaTeż) Action (October 2017) on Facebook - Bagiński , Paweł (Stan Rzeczy, 2019)
This paper considers how a truth discourse about violence against women was produced with the #JaTeż posts published on Facebook between 16 and 20 October 2017, during the first phase of Polish #MeToo. It applies a post-Foucauldian perspective of dispositive analysis to outline how the circulation of #MeToo (#JaTeż) in social media affected the patriarchal dispositive of gender, which had to give way to women speaking truth. The replication of posts and accumulation of affects in the #MeToo (#JaTeż) network allowed the normalisation of violence against women in public discourse to be countered. Michel Foucault’s work on parrhesiastic and confessional modes of truth-telling is employed to analyse courage and solidarity in #MeToo (#JaTeż), as well as to connect individual engagement in the action with the collective claim for a normative shift in favour of women’s rights.